1985
DOI: 10.1016/s0735-1097(85)80174-1
|View full text |Cite
|
Sign up to set email alerts
|

Intimal proliferation of smooth muscle cells as an explanation for recurrent coronary artery stenosis after percutaneous transluminal coronary angioplasty

Abstract: The pathologic changes in the coronary arteries of three patients who died 5, 17 and 62 days, respectively, after percutaneous transluminal coronary angioplasty were studied. Changes in the vessel wall seen early after angioplasty included focal denudation of the endothelium, splits in the intima extending to and along the inner aspect of the media, focal intimal necrosis and adventitial hemorrhage. Extensive medial dissections were seen in the coronary arteries of the two patients who died 5 and 17 days after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 561 publications
(115 citation statements)
references
References 7 publications
4
109
0
2
Order By: Relevance
“…Since in all experiments, regardless of the protocol used, oxalate caused significant inhibition of cellular replication, the results from all protocols have been combined in the data presented. 51 …”
Section: Quantification Of Cell Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since in all experiments, regardless of the protocol used, oxalate caused significant inhibition of cellular replication, the results from all protocols have been combined in the data presented. 51 …”
Section: Quantification Of Cell Replicationmentioning
confidence: 99%
“…For short-term experiments in which chromium release was studied, endothelial cells were incubated in medium containing 51 Cr (sodium chromate, 5 jiCi/ml; New England Nuclear, Boston, MA) for 3 hours and washed twice before use. For long-term experiments, cells were incubated with 51 Cr for 24 hours.…”
Section: Crmentioning
confidence: 99%
“…Although this process differs in various pathologic conditions, the traditional paradigm for the pathogenesis of neointimal hyperplasia stresses the migration of smooth muscle cells from the media to the intima (42,43). Recent evidence, primarily from models of arterial injury (coronary angioplasty and saphenous vein bypass grafting), have supported a concept whereby the adventitial layer of the vessel plays an active role in neointima formation characterized by the following events (14,15,(44)(45)(46): (1) adventitial activation of fibroblasts in response to endothelial cell injury; (2) adventitial proliferation and migration of fibroblasts from the adventitia, through the media, and into the intima, where these cells transform into myofibroblasts and vascular smooth muscle cells controlled by matrix metalloproteinases and local cytokines and growth factors; and (3) further proliferation of myofibroblasts and vascular smooth muscle cells within the intima, and synthesis of new extracellular matrix to form the lesion of neointimal hyperplasia.…”
Section: Cellular Phenotypes and Migration Of Cells In Neointima Formmentioning
confidence: 99%
“…The gradual development of the concept that restenosis was the end-result of an uncontrolled proliferation of tissue at the injury site laid the groundwork for radiation being tested in this area. 13,14,15,16 In vitro studies had demonstrated the inhibition of proliferation of arterial smooth muscle cells (SMC's) and fibroblasts as well as decreased collagen synthesis by fibroblasts. 17,18,19 The development of the porcine overstretch balloon injury model of restenosis has provided an excellent model in which to evaluate new therapies since as radiation.…”
Section: Introductionmentioning
confidence: 99%